Broadband and Firm Location: Some answers to relevant policy and research issues using meta-analysis - Duvivier, Chloé (Canadian Journal of Regional Science / Revue canadienne des sciences régionales)

(untitled) (Canadian Regional Science Association / Association canadienne des sciences régionales, 2019)
We provide a quantitative literature review on broadband and firm location. While most previous works find that broadband has positive effects on firm location, the impact is very heterogeneous across studies. We examine the role of three categories of variables (context, methodological choices and publication characteristics) in explaining the variation in previous estimates. The results indicate that broadband effects are significantly more beneficial in urban areas, whereas lesser effects are found for finance, real estate and insurance. Methodological settings, and particularly the choice of the level of analysis, of control variables and of the econometric estimator, also play a significant role in explaining the differences in previous estimates. These results are then discussed to find some answers to relevant policy and research issues.